The apraxia of speech rating scale: A tool for diagnosis and description of apraxia of speech - Strand, Edythe A.; Duffy, Joseph R.; Clark, Heather M.; Josephs, Keith (Journal of communication disorders, 2014)
•The ASRS quantifies the frequency/severity of the characteristics associated with AOS.•ASRS correlates with clinical diagnosis and severity of AOS.•Overall intra-judge and inter-judge reliability is acceptable.•Sensitivity and specificity of the ASRS are acceptable. The purpose of this report is to describe an initial version of the Apraxia of Speech Rating Scale (ASRS), a scale designed to quantify the presence or absence, relative frequency, and severity of characteristics frequently associated with apraxia of speech (AOS). In this paper we report intra-judge and inter-judge reliability, as well as indices of validity, for the ASRS which was completed for 133 adult participants with a neurodegenerative speech or language disorder, 56 of whom had AOS. The overall inter-judge ICC among three clinicians was 0.94 for the total ASRS score and 0.91 for the number of AOS characteristics identified as present. Intra-judge ICC measures were high, ranging from 0.91 to 0.98. Validity was demonstrated on the basis of strong correlations with independent clinical diagnosis, as well as strong correlations of ASRS scores with independent clinical judgments of AOS severity. Results suggest that the ASRS is a potentially useful tool for documenting the presence and severity of characteristics of AOS. At this point in its development it has good potential for broader clinical use and for better subject description in AOS research. Learning Outcomes: The Apraxia of Speech Rating Scale: A new tool for diagnosis and description of apraxia of speech1.The reader will be able to explain characteristics of apraxia of speech.2.The reader will be able to demonstrate use of a rating scale to document the presence and severity of speech characteristics.3.The reader will be able to explain the reliability and validity of the ASRS.